INTERVENSI WORK DESIGN DAN JOB CRAFTING UNTUK MENINGKATKAN MOTIVASI KERJA DAN KESIAPAN PERUBAHAN PADA KARYAWAN PT. PENGEMBANGAN PARIWISATA INDONESIA (PERSERO) - Yande Prayoga; Ni Putu Lilik Agestin; Kadek Putri Lestari Wardani; Ni Kadek Diah Shinta Kartika (Bajang Institute, 2026)
Abstract: Organizational transformation requires employee readiness to accept and adapt to change. This study aimed to design an organizational development intervention to improve employees’ attitude toward change at ITDC (Persero), a state-owned enterprise engaged in tourism destination development. The study employed an organizational diagnosis approach using the Organizational Diagnosis Questionnaire (ODQ), Job Diagnostic Survey (JDS), and interviews. Results indicated that the attitude toward change score (M = 4.26 on a 1–7 scale) was categorized as moderate and below the expected target (M ≥ 5.00). Approximately 58.8% of employees showed lower readiness for organizational change. Based on the diagnosis, a technostructural intervention through work design and job crafting approaches was proposed to enhance intrinsic motivation and psychological readiness for change. The intervention aimed to increase skill variety, autonomy, task significance, and feedback mechanisms. The study concludes that systematic organizational development interventions are essential in supporting sustainable corporate transformation